2003
DOI: 10.1097/00002371-200303000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tumor-Specific Antibodies in Patients With Breast Cancer Vaccinated With Gene-Modified Allogeneic Tumor Cells

Abstract: Summary: Thirty HLA-A2+ women with metastatic breast cancer received up to 14 vaccinations with MDA-MB-231-CD80, an HLA-A2 + allogeneic breast cancer cell line, which had been lipofected with the cDNA for the CD80 costimulatory molecule. Tumor cells were administered with BCG or GM-CSF as an adjuvant. Sera obtained before and after vaccination were analyzed for antibodies to tumor cell lysate, MUC1, HER2/neu and p53. Since the cell line was grown in fetal bovine serum (FBS), sera were also analyzed for antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 26 publications
2
12
0
2
Order By: Relevance
“…18,[21][22][23]40,41 In addition, some authors have reported differences in the serum protein composition between untreated and heavily pretreated patients, which may influence the differentiation process of DCs. 18,21,23 In accordance with the majority of reports in the literature, 16,39,42,43 similar yield of DCs was obtained in all culture conditions despite the presence or the absence of serum. DCs were characterized for the expression of HLA-DR, CD86, CD83, and CD14.…”
Section: Discussionsupporting
confidence: 88%
“…18,[21][22][23]40,41 In addition, some authors have reported differences in the serum protein composition between untreated and heavily pretreated patients, which may influence the differentiation process of DCs. 18,21,23 In accordance with the majority of reports in the literature, 16,39,42,43 similar yield of DCs was obtained in all culture conditions despite the presence or the absence of serum. DCs were characterized for the expression of HLA-DR, CD86, CD83, and CD14.…”
Section: Discussionsupporting
confidence: 88%
“…Studies with anti-CTLA-4 monoclonal antibodies, in particular, have sought to identify whether amplification of other T-cell co-stimulatory molecules (35), or antibodies to defined antigenic tumor-associated proteins (33,36), might be useful as biomarkers. For whole cell tumor vaccines where there is not a specific defined antigen being targeted, surrogate antigens known to be expressed by the tumor vaccine have been used as a means of monitoring immune responses from the vaccine (37). The use of immunologically-recognized surrogate antigens, including HER-2/neu, MUC1 and p53, has been possible in the case of breast cancer where IgG responses to these antigens have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…15,22 Five of 7 patients were strongly positive for antibodies to bovine apoB ( Figure 5D and Table 2), perhaps reflecting their extensive exposure in circumstances optimized for immunity. Finally, we examined the sera from HIV-infected patients administered enriched T-cell populations from their HIV-negative twin.…”
Section: Antibodies To Bovine Apob-100 Dominate the Human Immune Respmentioning
confidence: 99%